Bo Mmaruri: Bosadi - Makgekgenene, Legakwana (Michaelis School of Fine Art, 2022)
Post-colonial Botswana is analysed in this body of work as an anecdote. Its landscapes, history, culture, traditions, norms and identity are deconstructed and reconstituted in a heterotopia of my own making. Motivated by the decline in the momentum and visibility of Botswana's women's movements, the project asks how non-male resistance and self-determination has and can operate in Botswana, particularly in traditional and cultural spaces. In this work, I identify storytelling and folklore as a device that though culturally-specific, is reflected across nations on the continent, and so, allows a meditation on personal and national identity that is not restrictive or isolating as it must occur in constant reference to the culture(s) around it. Through my own works and the works of Thebe Phetogo, Meleko Mokgosi, Athi Patra-Ruga and Kudzanai Chuirai, I discuss the ‘making visual' of oral and folklore culture to highlight the interconnectedness of African narratives and oral storytelling/performing practices while deconstructing Botswana's conceptual basis, which this work sees as being folklore itself.